Diversity and Distribution Patterns of Epiphytic Orchid in the Nirmala Tea Plantation, Bogor West Java - Nurul Aini; Tatik Chikmawati; Sulistijorini Sulistijorini; Nina Ratna Djuita; Nunik Sri Ariyanti (Biosaintifika: Journal of Biology & Biology Education, 2022)
Tea plantations can provide microclimate conditions for many epiphytic species, including orchids, but information on their diversity is not yet available. Epiphytic orchid diversity study has been carried out at the Nirmala Tea Plantation, Bogor, West Java. The main objective of this study was to reveal the diversity of epiphytic orchids in the Nirmala Tea Plantation. The data were obtained by vegetation analysis using the purposive sampling method by making 54 plots sized 5 x 5m2 at two different altitudes, 1050 and 1500 masl. The quantitative data were analyzed by calculating the critical value and morisita indices. The correlation between epiphytic orchid and microclimate variables was processed using Spearman bivariate correlation, performed using Canonical Correspondence Analysis. A total of 15 epiphytic orchids were found at an altitude of 1050 m asl and 10 species of epiphytic orchids at an altitude of 1500 m asl. Seven species, Agrostophyllum longifolium Rchb.f., Appendicula reflexa Blume, Bulbophyllum sp.2, Dendrochilum sp., Eria sp.1, Flickingeria sp, Pholidota carnea Lindl, were found at both altitudes. The diversity of epiphytic orchids is affected by altitude, light intensity, and wind speed. The distribution pattern of epiphytic orchids in Nirmala Tea Plantation is clumped. The results of this study report the diversity of orchids grown in tea plantations for the first time. This information is helpful for the cultivation and conservation of orchid diversity in the future.